A pact of iron? China’s deepening of the Sino-Russian partnership - Morgado, Nuno; Hosoda, Takashi (Frontiers in Political Science, 2024)
To characterize the bilateral partnership, this paper applies the neoclassical geopolitics approach. We first measure China’s potential, and the perception of Chinese geopolitical agents, and placed within the international distribution of capabilities. This is followed by our analytical results on Sino-Russian relations in the spheres of potential, strategic culture, and geopolitical design. The paper concludes that while there is a strategic necessity for China to strengthen the partnership, the Sino-Russian relations are unlikely transforming into a traditional military alliance, due to Beijing’s self-interest to maintain trade relations with Western countries, to avoid being tainted by Russia’s deteriorating reputation, to grasp its goal of multipolar world order, and to spread positive narratives of China as a new global leader. The Sino-Russo relations has been shifting its nature from “marriage of convenience” to “marriage who pretend to be a good couple.”